"A certain kind of romanticism": an interview with Mike Parker. Issue 4 (2nd October 2017) - Richardson, Séan
ABSTRACT: In conversation on 12 September 2017 at his home in Machynlleth, Wales, writer Mike Parker discusses with Séan Richardson the politics of travel writing. Addressing topics from the Rough Guide to Plaid Cymru, queer history to the National Trust, Parker shows how even the simplest of journeys is subtly constructed by the symbols that guide our path, how travel writing goes beyond the written page and how our identities shape the places around us, as much these places shape our identities. With the humour and candour that cuts through his work, Parker unveils how travel is as much a communal experience as it is an individual one.